2018
DOI: 10.1016/j.amepre.2017.07.004
|View full text |Cite
|
Sign up to set email alerts
|

U.S. Preventive Services Task Force Methods to Communicate and Disseminate Clinical Preventive Services Recommendations

Abstract: The U.S. Preventive Services Task Force (USPSTF) issues evidence-based screening and prevention recommendations, and key to this task is dissemination and implementation of these recommendations. The Task Force has recommendations for more than 84 topics; each USPSTF Recommendation Statement includes a letter grade, a topline summary to guide clinician interpretation in practice, and a summary of gaps in evidence to help catalyze clinically relevant research. The USPSTF aims to update existing topics regularly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…These people, as much as the professionals, determine the legitimacy of screening interventions, be it by bringing political pressure to bear on the relevant authorities or simply by consenting or declining to participate in screening. Screening governance organizations are often active in communicating their conclusions and rationales widely and for diverse publics 29 , and there is evidence that active engagement may have a significant impact on public attitudes towards screening 30 . They may also have the capacity to provide opportunities for public input, for example through public membership of review committees, or stakeholder input on draft recommendations.…”
Section: Organizing Screening Governancementioning
confidence: 99%
“…These people, as much as the professionals, determine the legitimacy of screening interventions, be it by bringing political pressure to bear on the relevant authorities or simply by consenting or declining to participate in screening. Screening governance organizations are often active in communicating their conclusions and rationales widely and for diverse publics 29 , and there is evidence that active engagement may have a significant impact on public attitudes towards screening 30 . They may also have the capacity to provide opportunities for public input, for example through public membership of review committees, or stakeholder input on draft recommendations.…”
Section: Organizing Screening Governancementioning
confidence: 99%
“…The U.S. Preventive Services Task Force (USPSTF) was formed in 1984 as an expert, volunteer panel to develop evidence-based recommendations regarding preventive health interventions (U.S. Preventive Services Task Force, 2019). The mission of the USPSTF is to standardize and disseminate evidence-based preventive services to improve the overall health of the population (Kurth et al, 2018). Despite extensive dissemination efforts, variations in clinical practice and implementation gaps remain.…”
Section: Us Preventive Services Task Force Recommendationsmentioning
confidence: 99%
“…Additional implementation and translational research will increase the value of the USPSTF's work and would be helpful in its deliberations. 21 For many important health problems, including obesity, cardiovascular disease, and drug and alcohol misuse, effective prevention requires programs of care that are sustained, intensive, and multimodal and that use interprofessional approaches. A high priority for research is how to adapt complex interventions that have demonstrated effectiveness in healthcare settings with advanced systems and resources to real-world clinical settings.…”
Section: Evidence Gaps In Implementing Recommendationsmentioning
confidence: 99%